Novosti in izzivi po sprejeti Direktivi o platformnem delu - Polajžar, Aljoša (Delavci in delodajalci, 2025)
The author discusses the content of the adopted Platform Work Directive and the future challenges related to its implementation. The author notes that the Directive addresses the areas of the fundamental concepts of platform work, the legal status of intermediaries in platform work, the determination of the correct employment status of platform workers, the legal regulation of algorithmic management, health and safety at work, and collective rights. A key challenge for the legislator will be to determine the content of the rebuttable legal presumption of the existence of an employment relationship of platform workers. The final version of the Directive no longer contains detailed criteria for the existence of the presumption.
Keywords: algoritemsko upravljanje; algorithmic management; delavski predstavniki; delovna razmerja; Delovno pravo; Direktiva o platformnem delu; inšpektorat za delo; Labour Inspectorate; platform work; platform workers; platformni delavci; platformno delo; presumption of the existence of an employment relationship; workers’ representatives